Tung tree stearoyl‐acyl carrier protein Δ9 desaturase improves oil content and cold resistance of Arabidopsis and Saccharomyces cerevisiae - Chen, Junjie; Gao, Jing; Zhang, Lingling; Zhang, Lin (Frontiers in Plant Science, 2023)
The seed oil of tung tree is rich in α-eleostearic acid (ESA), which endows tung oil with the characteristic of an excellently dry oil. The stearoyl-acyl carrier protein Δ9 desaturase (SAD) is a rate-limiting enzyme that converts the stearic acid to the oleic acid, the substrate for the production of the α-ESA. However, the function of the two predicted VfSAD1 and VfSAD2 genes in the tung tree has not been determined. QRT-PCR analysis showed that the VfSAD1 and VfSAD2 were expressed in multiple organs of tung tree, but were highly expressed in the seed during the oil rapid accumulation period. The VfSAD1 and VfSAD2 possess the stearoyl-ACP desaturases function, both which could promote the production of the oleic acid and its derivations by heterologous expression in the Arabidopsis and yeast BY4741 strain. Furthermore, both of VfSAD1 and VfSAD2 could significantly improve seed oil accumulation in Arabidopsis. And VfSAD1 could also significantly promote the oil accumulation in the yeast BY4741 strain. Besides, overexpression of VfSAD1 and VfSAD2 enhanced the tolerance of yeast and Arabidopsis seedlings to the low temperature stress. This study indicates that the two VfSAD genes play a vital role in the process of oil accumulation and fatty acid biosynthesis in the tung tree seed, and both of them could be used for molecular breeding in tung tree and other oil crops.